2017
DOI: 10.3748/wjg.v23.i30.5567
|View full text |Cite
|
Sign up to set email alerts
|

Serous pancreatic neoplasia, data and review

Abstract: AIMTo describe the imaging features of serous neoplasms of the pancreas using ultrasound, endoscopic ultrasound, computed tomography and magnetic resonance imaging.METHODSThis multicenter international collaboration enhances a literature review to date, reporting features of 287 histologically confirmed cases of serous pancreatic cystic neoplasms (SPNs).RESULTSFemale predominance is seen with most SPNs presenting asymptomatically in the 5th through 7th decade. Mean lesion size was 38.7 mm, 98% were single, 44.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 78 publications
1
11
0
1
Order By: Relevance
“…These results are in concordance with the findings published for more than 1,000 histologically proven focal pancreatic lesions and in earlier studies using CEUS techniques [29,49]. Eye-catching features have been published for the imaging of serous microcystic neoplasia with only microscopically detectable cysts mimicking a solid lesion [66].…”
Section: Contrast-enhanced Ultrasonography And/or Contrast-enhanced Esupporting
confidence: 91%
“…These results are in concordance with the findings published for more than 1,000 histologically proven focal pancreatic lesions and in earlier studies using CEUS techniques [29,49]. Eye-catching features have been published for the imaging of serous microcystic neoplasia with only microscopically detectable cysts mimicking a solid lesion [66].…”
Section: Contrast-enhanced Ultrasonography And/or Contrast-enhanced Esupporting
confidence: 91%
“…The summary sensitivity was 81% (95% CI: 71-88) and the specificity was 91% (95% CI: [83][84][85][86][87][88][89][90][91][92][93][94][95][96] for the prediction of significant liver fibrosis. Subgroup analysis revealed that 2D-SWE had an excellent diagnostic performance according to each degree of liver fibrosis.…”
Section: Technical Success Rates Of Liver Stiffness Estimatesmentioning
confidence: 99%
“…Real-time elastography (RTE) has been used mainly for the evaluation of the pancreas [83][84][85][86], the thyroid [87][88][89][90][91][92][93][94], the prostate [95], the breast [5,96] but also for the liver [1,2,7,97]. Published evidence in children is scarce and contradictory [98][99][100].…”
Section: Strain Imaging (Real-time Elastography (Rte))mentioning
confidence: 99%
“…Pancreatic pseudocyst may simulate clinically and radiologically with other cystic neoplasms of the pancreas. Serous cystic neoplasm (SCN) mostly affects females of the sixth or seventh decade of life and favors the body and tail of the pancreas [ 12 ]. Central stellate scar, sunburst calcification, lobulated appearance, septations, and micro or macrocysts are characteristic features of SCN [ 13 ].…”
Section: Discussionmentioning
confidence: 99%